Design and implementation of secure Windows platform based on TCM - Wei FENG; Yu QIN; Deng-guo FENG; Bo YANG; Ying-jun ZHANG (Tongxin xuebao)
A secure Windows platform solution based on TCM was proposed to solve the integrity measurement and attestation problem of the Windows system.Two security modes were realized by extending the Windows kernel:in the measurement mode,all executable contents that were loaded onto the Windows system were measured,and the TCM provided the protection and outward attestation for these measurements; and in the control mode,the measurements were further compared with a whitelist customized by an administrator,and all the programs that were not included in the whitelist would be prohibited from running.Experiment analysis shows that proposed solution can enhance the security of Windows platform and resist some software attacks; and at the same time,the average performance overhead is about 20～30ms,which will not influence the normal running of Windows.